Improving on medication adherence using Diabetes Little Helper video among elderly patients with type 2 diabetes mellitus - Wang, Meng; Lee, Khuan; Thew, Hui Zhu; Sowtali, Siti Noorkhairina; Jiang, Qiuhuan; Lim, Poh Ying (2023)
The prevalence of type 2 diabetes mellitus (T2DM) in the elderly is increasing pattern. Treatment efficacy among T2DM can be ensured by through good medication adherence. which can effectively minimize complications, reduce medical costs, and improve quality of life. There is limited intervention studies in China, on improving the medication adherence among T2DM elderly. This study aims to develop and implement the Diabetes Little Helper Video Intervention based on Information-Motivation-Behavioral Skills (IMB) model and evaluate its effectiveness on medication adherence among elderly T2DM patients in Zhengzhou, Henan, China. This study is cluster parallel randomized controlled trial, involved two hospitals with a sample size of 87 participants per group [Intervention group (IG) and Control group (CG)]. The CG will receive standard care, while the IG will receive 12 video intervention together with standard care (three video per weeks). The 12 video content was developed based on IMB model, with topics related with knowledge and attitude on medication adherence, medication belief, proper ways of using medication, storage of medication and other topics related with medication. First round of content validity was done among experts to ensure the topics of module are acceptable and related with objectives of this study. Data collection will be conducted at baseline, post intervention, 3 months post intervention, using self-administrative questionnaire. Generalized estimating equation statistical test will be used to analyze the effectiveness of Diabetes Little Helper Video Intervention on medication adherence at different time points, adjusted with covariates. Expected outcome of this study is to ensure that Diabetes Little Helper Video Intervention significantly improve the level of medication adherence, eventually can reduce the complication and improve the treatment efficacy.